Wi-Fi Supported Networked Computer-on-Module for IoT - Zeng, Xianping (fi=Turun yliopisto|en=University of Turku|, 2018)
With the arrival of Internet of Things (IoT) era, a large number of IoT based applications are springing up. It is estimated that the number of IoT devices will reach to 20-200 billion. Wi-Fi has been widely used in the past decade because of the high data transmission rate, wide signal coverage and low radiation. By using the existing Wi-Fi network resources to implement IoT communication, the device cost can be dramatically reduced. In this thesis work, aiming to provide a low cost low power IoT solution with high flexibility and shorten product development time, a Wi-Fi supported networked Computer-on-Module (COM) is designed. It adopts an ultra-low-power and reconfigurable Application Specific Instruction Set Processor (ASIP)—FC3180 and a WLAN SoC designed by Marvell—88W8686, which are connected over SPI bus. To enable Wi-Fi connectivity in software, WLAN driver and IEEE 802.11 network stack are developed in C language. The Wi-Fi driver is implemented into five parts: SPI interface driver, firmware management, control flow, data path, and TCP/IP stack interface. In order to improve the system performance, the WLAN driver is optimized in several ways during development. In the IEEE 802.11 network stack, a WPA/WPA2-PSK supplicant is implemented to add the support for the Wi-Fi networks using WPA/WPA2-PSK encryption mode. In order to verify the system functionality, a prototype of the COM is manufactured and is applied in a sensor system. Tests on the COM are carried out in the sensor system and the experimental results show that the system works properly.